Outcome for children and young people with Early T‐cell precursor acute lymphoblastic leukaemia treated on a contemporary protocol, UKALL 2003. (8th April 2014) - Patrick, Katharine; Wade, Rachel; Goulden, Nick; Mitchell, Chris; Moorman, Anthony V.; Rowntree, Clare; Jenkinson, Sarah; Hough, Rachael; Vora, Ajay
Summary We investigated the outcome for children and young people with Early T‐precursor acute lymphoblastic leukaemia (ETP‐ALL), a recently described poor prognosis sub‐group of T‐ALL, treated on a contemporary protocol, UKALL 2003. After a median follow‐up of 4 years and 10 months, the ETP sub‐group, representing 16% of T‐ALL patients, had non‐significantly inferior 5‐year event‐free survival (76·7% vs. 84·6%, P = 0·2) and overall survival (82·4% vs. 90·9%, P = 0·1), and a higher relapse rate (18·6% vs. 9·6%, P = 0·1) compared to typical T‐ALL. ETP‐ALL has an intermediate risk outcome, which does not warrant experimental treatment or first remission allogeneic transplant for the group universally.